Statistical Convergence of Double Sequences of Order - R. Çolak; Y. Altin (Journal of Function Spaces and Applications)
We intend to make a new approach and introduce the concepts of statistical convergence of order and strongly -Cesàro summability of order for double sequences of complex or real numbers. Also, some relations between the statistical convergence of order and strong -Cesàro summability of order are given.